THE USE OF EMPAGLYFLOSINE IN PATIENTS WITH CHRONIC CARDIAC FAILURE AND DYSFUNCTION OF THE KIDNEYS - G.A, Khudoyberdiyeva; N.R. , Raimkulova (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aimed to evaluate the effects of empagliflozin on carbohydrate metabolism and lipid profile in patients with chronic heart failure and kidney dysfunction. Method: A total of 54 patients were enrolled and received empagliflozin therapy for six months. Clinical parameters, including fasting glucose, glycated hemoglobin (HbA1c), insulin levels, total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides, and glomerular filtration rate (GFR), were measured before and after treatment to assess metabolic and renal outcomes. Results: The findings demonstrated significant reductions in glucose, HbA1c, insulin, total cholesterol, LDL, and triglycerides, alongside an increase in HDL levels, while GFR remained stable throughout the treatment period. These outcomes suggest favorable metabolic modulation without deterioration of renal function. Novelty: This study provides novel clinical evidence supporting the dual cardiometabolic benefits of empagliflozin in patients with concurrent heart failure and renal impairment, emphasizing its therapeutic potential beyond glycemic control in improving overall metabolic health and cardiovascular protection.